7x+3(x-2)=6(x+1)-3

Simple and best practice solution for 7x+3(x-2)=6(x+1)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+3(x-2)=6(x+1)-3 equation:


Simplifying
7x + 3(x + -2) = 6(x + 1) + -3

Reorder the terms:
7x + 3(-2 + x) = 6(x + 1) + -3
7x + (-2 * 3 + x * 3) = 6(x + 1) + -3
7x + (-6 + 3x) = 6(x + 1) + -3

Reorder the terms:
-6 + 7x + 3x = 6(x + 1) + -3

Combine like terms: 7x + 3x = 10x
-6 + 10x = 6(x + 1) + -3

Reorder the terms:
-6 + 10x = 6(1 + x) + -3
-6 + 10x = (1 * 6 + x * 6) + -3
-6 + 10x = (6 + 6x) + -3

Reorder the terms:
-6 + 10x = 6 + -3 + 6x

Combine like terms: 6 + -3 = 3
-6 + 10x = 3 + 6x

Solving
-6 + 10x = 3 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-6 + 10x + -6x = 3 + 6x + -6x

Combine like terms: 10x + -6x = 4x
-6 + 4x = 3 + 6x + -6x

Combine like terms: 6x + -6x = 0
-6 + 4x = 3 + 0
-6 + 4x = 3

Add '6' to each side of the equation.
-6 + 6 + 4x = 3 + 6

Combine like terms: -6 + 6 = 0
0 + 4x = 3 + 6
4x = 3 + 6

Combine like terms: 3 + 6 = 9
4x = 9

Divide each side by '4'.
x = 2.25

Simplifying
x = 2.25

See similar equations:

| 2(k+5)-3=k+18 | | Y=-3(-6)+5 | | 6x^2-2=135 | | 7x-2=7(x+4) | | 5wk-3k-6k+k-10= | | 7x+8-6x=3 | | -4+2y=3y-6 | | 22-10n+n^2=-2 | | -7m+13+8m-5= | | 7=3z+2 | | 7x+8-6x+3= | | 2y-6=11y+57 | | -22x-1x= | | (x+5)(x-9)=(2x+7)(x-5) | | ax-b=4x-7 | | .5x+.45(30)=49.5 | | -8m+15+9m=-2 | | Y=-4(4)-3 | | x-9+5x-3=5x | | 11x=10x+17 | | Y=-4(-2)-3 | | x-14.6=20 | | 5(k+2)=3(-4) | | -8m+15+9m-2= | | Y=-10(5)-3 | | n+221=333 | | 5m-13=33 | | 9x^4=3x^2-25 | | 5(5x)+12= | | 5(5x+12)= | | 4n+24=2n+42 | | 3p+5=2p+14 |

Equations solver categories